Ultrasound-generated bubbles enhance osteogenic differentiation of mesenchymal stromal cells in composite collagen hydrogels - Somnath Maji; Mitra Aliabouzar; Carole Quesada; Anjali Chiravuri; Aidan Macpherson; Abigail Pinch; Karsyn Kazyak; Ziyad Emara; Bachir A. Abeid; Robert N. Kent, III; Firaol S. Midekssa; Man Zhang; et al. (Bioactive Materials)
Hydrogels can improve the delivery of mesenchymal stromal cells (MSCs) by providing crucial biophysical cues that mimic the extracellular matrix. The differentiation of MSCs is dependent on biophysical cues like stiffness and viscoelasticity, yet conventional hydrogels cannot be dynamically altered after fabrication and implantation to actively direct differentiation. We developed a composite hydrogel, consisting of type I collagen and phase-shift emulsion, where osteogenic differentiation of MSCs can be non-invasively modulated using ultrasound. When exposed to ultrasound, the emulsion within the hydrogel was non-thermally vaporized into bubbles, which locally compacted and stiffened the collagen matrix surrounding each bubble. Bubble growth and matrix compaction were correlated, with collagen regions proximal (i.e., ≤ ∼60 μm) to the bubble displaying a 2.5-fold increase in Young's modulus compared to distal regions (i.e., > ∼60 μm). The viability and proliferation of MSCs, which were encapsulated within the composite hydrogel, were not impacted by bubble formation. In vitro and in vivo studies revealed encapsulated MSCs exhibited significantly elevated levels of RUNX2 and osteocalcin, markers of osteogenic differentiation, in collagen regions proximal to the bubble compared to distal regions. Additionally, alkaline phosphatase activity and calcium deposition were enhanced adjacent to the bubble. An opposite trend was observed for CD90, a marker of MSC stemness. Following subcutaneous implantation, bubbles persisted in the hydrogels for two weeks, which led to localized collagen alignment and increases in nuclear asymmetry. These results are a significant step toward controlling the 3D differentiation of MSCs in a non-invasive and on-demand manner.